2020
DOI: 10.1101/2020.05.30.20117929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic Anticoagulation Is Associated with Decreased Mortality in Mechanically Ventilated COVID-19 Patients

Abstract: Objective: To evaluate differences in morbidity and mortality among mechanically ventilated patients with COVID-19 treated with therapeutic versus prophylactic anticoagulation. Methods: We performed a retrospective review of 245 COVID-19 positive patients admitted to the ICU requiring mechanical ventilation from March 1, 2020 through April 11, 2020 at Mount Sinai Hospital. Patients either received therapeutic anticoagulation for a minimum of 5 days or prophylactic dose anticoagulation. Morbidity and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 22 publications
2
43
1
Order By: Relevance
“…Frequencies in our cohort are higher, but comparable to those reported by Nadkarni et al (3% and 1.7% for those receiving tAC and pAC respectively, compared to 1.9% in the no AC group) 11 . Trinh et al reported markedly higher rates of bleeding events in critically ill patients, especially in the tAC vs pAC groups (31.7% vs 20.5%; P = .07) 14 . While the benefit of tAC came at the cost of more bleeding, the rate of intracranial bleed as evidenced on cranial imaging was similar between the tAC and no AC groups (1.3% vs 1.1%).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Frequencies in our cohort are higher, but comparable to those reported by Nadkarni et al (3% and 1.7% for those receiving tAC and pAC respectively, compared to 1.9% in the no AC group) 11 . Trinh et al reported markedly higher rates of bleeding events in critically ill patients, especially in the tAC vs pAC groups (31.7% vs 20.5%; P = .07) 14 . While the benefit of tAC came at the cost of more bleeding, the rate of intracranial bleed as evidenced on cranial imaging was similar between the tAC and no AC groups (1.3% vs 1.1%).…”
Section: Discussionmentioning
confidence: 94%
“…The first study by Paranjpe et al found similar in‐hospital mortality rates between patients treated with tAC and those who were not (22.5% vs 22.8%), a longer median survival time in the tAC group (21 days vs 14 days), and an association between tAC duration and reduced risk of death (HR, 0.86 per day [95% CI 0.82‐0.89]) 13 . Subsequently, Trinh et al reported a 79% decrease in the risk of death in patients treated with at least 5 days of tAC compared to pAC (HR, 0.209 [95% CI 0.1‐0.46]) in critically ill patients belonging to the same cohort and 14 . Most recently, Nadkarni et al expanded the existing cohort to nearly 4400 subjects and specifically investigated the impact of tAC and pAC compared to patients who did not receive AC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While only 1 study showed a statistically-significant increase in the bleeding risk among patients treated with therapeutic-dose anticoagulation, 20 2 other studies also showed an increase among those receiving this treatment, although this was not significant. 12,13 A larger sample size in the study could have led to a statisticallysignificant result. Therefore, we propose that the use of therapeutic-dose anticoagulation must be further elucidated in the settings of larger propensity-matched prospective cohorts or randomized controlled trials before its implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…Ultimately, 8 studies were included in the final qualitative synthesis (Figure 1). [12][13][14][15][16][17][18][19][20] The main features of the 8 studies are presented in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%